The stigma of electroconvulsive therapy - Rigonatti, Sérgio Paulo (2011)
Electroconvulsive therapy is a safe and effective form of treatment, but it is surrounded by myths and misconceptions. Such ideas are the result of outdated stigmas and ignorance, perpetuated by certain groups motivated by private interests. Education is the best way to reverse this situation and expand the use of this tool.